ASUHAN KEPERAWATAN GERONTIK PADA GANGGUAN KOGNITIF DEMENSIA DENGAN BRAIN GYM EXERCISE DI UPT PELAYANAN SOSIAL LANJUT USIA BINJAI - Sijabat, R. Sri Rezeki; Pangaribuan, Resmi; Tarigan, Jemaulana (LPPM Institut Pendidikan Nusantara Global, 2024)
Background:According to the World Health Organization(WHO,2018),approximately 50 million people suffer from dementia,with nearly 60%residing in low and middle-income countries.Each year, there are almost 10 milion new cases.The total number of dementia patients worldwide is projected to reach 82 million by 2030 and 152 million by 2050.Dementia is a symptom of declining memory. thinking,behavior,and the ability to perform daily activities.An individual is considered to have dementia when experiencing mental disturbances in at least two brain functions.One effort to prevent cognitive decline in the elderly is by engaging in Brain Gym Exercise. Method: This research is a case study with a descriptive research design following the nursing care process for the elderly.The focus of this case study is on two elderly individuals diagnosed with dementia.Study subjects were selected based on inclusion and exclusion criteria,then an intervention was conducted for 3 days by providing nursing care action in the form of Brain Gym Exercise for 15 minutes once a day.Data collection was done through interviews,observations,and nursing care.Cognitive function was measured using the Mini-Mental State Exam(MMSE)instrument. Results: After conducting Brain Gym Exercise for 15 minutes once a day for the two elderly respondents,the research results indicated that brain exercises can enhance cognitive function in elderly dementia patients,as shown by increased MMSE scores in both study subjects. Conclusion: After a 3-day brain exercise intervention,the MMSE scores increased within the range of 0-17,and both respondents were able to perform it.